Cervical Length Ultrasound for the Evaluation of Preterm Labor: A Survey of National Use and Review of Evidence - Boelig, Rupsa C.; Mcintosh, Jennifer; Feltovich, Helen; House, Michael (American Journal of Perinatology, 2022)
Objective The objective of this study was to survey national utilization of cervical length (CL) ultrasound on labor and delivery (L&D) for the evaluation of preterm labor (PTL) and identify provider attitudes and barriers to utilization.Study Design Survey was emailed to Obstetrics and Gynecology Residency and Maternal-Fetal Medicine Fellowship program and advertised via links on obstetric-related Facebook interest groups. The survey was open from August 4, 2020 to January 4, 2021. Characteristics between respondents who did and did not report the use of CL ultrasound for PTL evaluation were compared with chi-square analysis.Results There were 214 respondents across 42 states. One hundred and thirty-four respondents (63%) reported any use of CL in the evaluation of PTL and eighty (37%) denied it. There was a significant difference in practice location, practice type, delivery volume, and region between those who did and did not utilize CL ultrasound on L&D. Those who did use CL ultrasound were more likely to report no barriers to use (40 vs. 4%, p < 0.001). The most common barriers involved the availability of transvaginal ultrasound (31%), sterilization of transvaginal ultrasound probe (32%), limited availability of persons able to perform/interpret CL imaging (38%). Nineteen percent believed CL ultrasound had little/no utility in clinical practice. Those who did not use CL ultrasound in the evaluation of PTL were significantly more likely to report the feeling that there was little/no utility of CL ultrasound in clinical practice (37 vs. 7%, p < 0.001) and to report transvaginal ultrasound availability as barriers to use (63 vs. 12%, p < 0.001).Conclusion CL ultrasound is used nationally in PTL evaluation. However, significant barriers limit widespread adoption. These barriers can be addressed through the dissemination of information and practice guidelines, addition of CL ultrasound education in residency training and through CME opportunities after training, and providing support/resources/access for those looking to add this tool to their practice environment.Key Points
Keywords: Cervical Length; preterm labor; preterm birth; research; cervical length ultrasound